Ecological Apparency Hypothesis and Plant Utility in the Semiarid Region of Brazil - Guerra, Natan Medeiros; Carvalho, Thamires Kelly Nunes; Ribeiro, João Everthon da Silva; Ribeiro, João Paulo de Oliveira; Barbosa, Abraão Ribeiro; Lima, José Ribamar de Farias; Alves, Carlos Antônio Belarmino; Oliveira, Rodrigo Silva de; Lucena, Reinaldo Farias Paiva de (Ethnobotany Research and Applications, 2015)
The ecological apparency hypothesis seeks to understand the dynamics of use that a particular species has through its availability in vegetation areas. According to this hypothesis, apparent plants are the most collected and used by humans. This hypothesis was tested in the rural community of Santa Rita, municipality of Congo, in Cariri microregion (Paraíba state, Northeast Brazil). We calculated the use value (UV) for each species. For the phytosociological inventory, we adopted the point-quadrant method, plotting 500 points distributed in the vegetation areas of the community, registering the perimeter measurements and height of 2000 plants. Interviews were conducted with householders, totaling 98 informants (41 men and 57 women), and 24 species, 21 genera, and 11 families were recorded. The cited species were grouped into 11 utility categories. The Spearman correlation coefficient was used to correlate phytosociological and ethnobotanical data. The use values of the species did not correlate with phytosociological parameters. Regarding the use categories, there were positive correlations for fuel (UV with dominance and basal area), construction (UV with all phytosociological parameters), fodder (UV with all parameters), and poison/abortion categories (UV with density and frequency). Ecological apparency significantly explained the local importance of useful plants in fuel, construction, and fodder categories, and less significantly for poison/abortion.